Differences in motor abilities between blind students and students without visual impairment - Ivana Zečević; Danijela Ilić-Stošović; Аleksandra Grbović (Exercise and Quality of Life)
The purpose of this study was to determine the level of motor abilities development in blind students and students without visual impairments, as well as to examine whether there are differences in motor abilities development between these two groups of participants. The research included 22 blind student (11 girls and 11 boys) and 22 students without visual impairments, aged 11-17 years. The Bruininks-Oseretsky Test of Motor Proficiency (BOT-2) was used to assess motor abilities. The analysis of the results revealed that the motor abilities development of blind students was significantly below average, while students without visual impairments showed an average level of motor abilities development. When comparing the achievements of blind students and students without visual impairments, it was observed that blind students had poorer performance on both the overall motor test and the subtests of bilateral coordination, upper limb coordination, and balance. On the other hand, students without visual impairments achieved good results on all tested subtests.